The Effects of Wars on Postwar Homicide Rates: a Replication and Extension of Archer and Gartner’s Classic Study - Stamatel, Janet P. (Journal of contemporary criminal justice, 2018)
This study replicates and extends Archer and Gartner’s classic work testing whether wars increase postwar homicide rates because they legitimize the use of violence as a means of conflict resolution. Using the Comparative Crime Data File (CCDF), we replicated the original study with data from the two World Wars, as well as 12 smaller wars occurring prior to 1980. Our replication results generally confirmed the hypothesis that wars increase postwar homicide rates, although there were differences in results based on the method of analysis. We then examined the validity of this theory using data on four wars occurring after 1990, but found no support for the legitimation of violence argument. We argue that the null findings encourage theoretical expansion, which is an underappreciated aspect of replication that is just as valuable as empirical validation.